PERANAN MEDIATOR DALAM PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL : (STUDI KASUS DI DINAS TENAGA KERJA KABUPATEN BOGOR) - Yesi Dewita Sari; Eriska Agustina (Economicus : Jurnal Ekonomi dan Manajemen, 2021)
This study was conducted to determine the role of mediators in resolving industrial relations disputes and how the PHI process at the Bogor Regency Manpower Office has rights, pleasure, no termination of employment, and relations between workers/unions can be resolved through two channels through the courts and outside. court. This research is a qualitative descriptive study. The focus of this research is the role of the mediator in resolving the cases experienced. The type of mediator used in this study is the type of authoritative mediator. Processing the validity of the data using triangulation techniques. Credibility, Transferability, Confirmability and Dependability. Data analysis and processing used in this study are: (1) data collection, (2) data reduction, (3) data presentation, (4) drawing conclusions or levers. The results showed that the role of the mediator in the settlement of industrial relations is in accordance with Law No. 2 of 2004 and Ministerial Decree No. 92 of 2004, to maximize the role of mediators in the settlement of industrial relations, the Bogor Regency Manpower Office provides special policies such as facilitate the disputing parties in holding negotiations beforehand. In the mediation process, the mediator uses the half-room technique in the process of carrying out the mediation session.